A Novel Gene Prognostic Signature Based on Differential DNA Methylation in Breast Cancer - Zhu, Chunmei; Zhang, Shuyuan; Liu, Di; Wang, Qingqing; Yang, Ningning; Zheng, Zhewen; Wu, Qiuji; Zhou, Yunfeng (Frontiers in Genetics, 2021)
Background: Accumulating studies have shown that DNA methylation played essential roles in regulating gene expression in breast cancer. Yet, the impacts of DNA methylation on breast cancer prognosis remain incompletely illustrated. Materials: Based on Illumina Human Methylation450 BeadChip array of TCGA, we developed a methylation prognostic model with multivariate Cox analysis. Subsequently, we further screened out the DEGs from methylation high-risk and low-risk groups and construct a methylation-related 6-gene prognostic signature. Results: Our study proposed 6-gene prognostic signature based on the methylation high- and low-risk groups. These two models were positively correlated with each other and both of them could predict the 3- and 5-year prognoses of BC more accurately than traditional clinical predictors. Moreover, three subgroups of TCGA datasets and an external dataset GSE146558 were successfully validating the methylation-related gene prognostic signature. And we also successfully validated the six prognostic genes in mRNA and protein levels. Conclusion: Our study proposed new prognostic models which could predict the prognoses of BC more accurately than traditional clinical predictors, and the six prognostic genes of gene prognostic signature may act as potential prognostic biomarkers and therapeutic targets.